Administration of human chorionic gonadotropin to embryo transfer recipients increased ovulation, progesterone, and transfer pregnancy rates - Wallace, Logan D. (Kansas State University, 2010)
We hypothesized that administration of human chorionic gonadotropin (hCG) to recipients at embryo transfer (ET) would induce accessory corpora lutea (CL), increase circulating progesterone concentrations, and reduce early embryonic loss. At three locations, purebred and crossbred Angus, Simmental, and Hereford recipients (n = 719) were assigned alternately to receive i.m. 1,000 IU hCG or 1 ml saline (control) at ET. Fresh or frozen-thawed embryos were transferred on d 5.5 to 8.5 (median = d 7) of the estrous cycle to recipients having a palpable CL. Recipients received a body condition score (BCS) at ET. Pregnancy diagnoses occurred by transrectal ultrasonography 28 to 39 d (median = d 35) and reconfirmed 58 to 77 d (median = d 67) post-estrus. At one location (n = 108), ovaries were examined to count the number of CL at pregnancy diagnosis. More (P < 0.001) pregnant hCG-treated cows (69.0%) had multiple CL than pregnant controls (0%). Serum progesterone (ng/mL) determined at two locations (n=471) at both pregnancy diagnoses in pregnant cows was greater (P ≤ 0.05) after hCG treatment than in controls (first: 8.1 ± 0.9 vs. 6.1 ± 0.8; second: 8.8 ± 0.9 vs. 6.6 ± 0.7), respectively. Transfer pregnancy rates were analyzed using logistic regression. Unadjusted pregnancy rates at the first diagnosis was 61.8 vs. 53.9% for hCG vs. controls. At the second diagnosis, pregnancy rates were 59.0 vs. 51.4%, respectively. Factors affecting pregnancy rates were treatment (P = 0.03), embryo type (P = 0.02), and BCS (P = 0.08). Odds ratios indicated that greater pregnancy rates occurred in recipients receiving hCG treatment, receiving a fresh embryo (66.3 vs.55.5%), and when BCS >5 vs. ≤5 (62.3 vs. 55.3%). We concluded that hCG at ET increased incidence of accessory CL, increased progesterone in pregnant recipients, and increased transfer pregnancy rates.
Keywords: Embryo transfer; hCG; Pregnancy rates; Agriculture, General (0473)